Analytic study of gastric epithelial polyps diagnosed by gastroduodenoscopy - سعيد, محمد; اسماعيل حمّاد; علي داؤود (Latakia University Journal -Medical Sciences Series, 2023)
Materials and Methods : we conducted across sectional analytical study of all gastroduodenoscopies performed at tishreen university hospital between (April 2021)and (April 2022) . 1669 patients had undergo gastroduodenoscopy ,and 55 patients were included in this study .clinical, endoscopic finding , and histopathological results were analyzed. Results: A total of 1669 patients underwent gastroduodenoscopy ,of these 55 patients gastric polyps (3,29%). 30 patients (54,55%) were females ,and 25 patients(45,45%) were males. The median age was (56.8±11.9) . Gastric polyps were found most commonly in the antrum (40%) and (89%) were ≤ 10mm. Histopathologic evaluation showed that hyperplastic polyps were the most common type (58.2%) followed by adenomatous polyps(11%) . -Non polyp- gastric mucosa evaluation revealed that( 45.45%) of the cases were Helicobacter pylori positive,(12.7%) had intestinal metaplasia ,and( 18,18 % )had atrophic gastritis . hyperplastic polyps were significantly associated with positive helicobacter pylori status compared with other polyp types ,and there was a statistically significant relationship between hyperplastic polyps size and location. Conclusion: In our study ,the gastric polyps prevalence was( 3.29%) . Hyperplastic polyps were the most common type , and it was associated with positive helicobacter pylori status which has a high prevalence in our country.